ADSORPTION OF TOFU WASTE USING WATER HYACINTH LEAVES POWDER FOR DECREASING BOD AND COD - Doni Rahmat Wicakso; Tutang Kania Koswartin; Wahyu Hardianto (Universitas Lambung Mangkurat, 2017)
Abstract- Water hyacinth leaves can be utilized in the process of adsorbing organic substances. This study aims to determine the decrease of COD and BOD maximum levels, the optimum mass of water hyacinth leaves powder that used and the optimum adsorption time. This research was done by adsorbing the tofu waste using adsorbent from water hyacinth leaves powder. Adsorption process used the adsorbent mass variation of 2.8; 3.2; 3,4 and 4 gram, and variation of adsorption time is 15, 30, 45, and 60 minutes. The results of adsorption process are then centrifuged, the residue and filtrate will be separated. Then calculated the value of BOD and COD from the filtrate. The decreasing in COD levels in the variation of mass obtained 0; 13.63%; 27.27%; 27.27% and 40.91%, while the decreasing in BOD content was 0; 33.33%; 46.67%; 55.56%; and 73,33%, indicating that the more adsorbent in the tofu waste will decrease the value of BOD and COD while the decreasing of the level will be bigger. The optimum mass analysis results obtained 4 grams on the decrease of BOD and COD. The optimum time of adsorption at COD was 30 minutes while there’s no equilibrium in BOD. Keywords: biomass, water hyacinth leaves, tofu waste.